THE CULTURAL COMPETENCES FORMATION FOR YOUTH - Burko, Olga (Educological discourse, 2019)
The article deals with the issue of honoring Borys Grinchenko's pedagogical and artistic work by Canadian teachers; Borys Grinchenko's handwritten magazine, «What does our school prepare for?» about the effectiveness of his teaching, was put into circulation; the model of cultural competences formation for students of the University and high school, is drawn up. The principle of dialogism and creativity are the basis of the author's concept. According to this, on the basis of the heuristic method, the following dialog task was introduced: to simulate the imaginary dialogue between excursionists and participants of the master-class and the workshop with B. Grinchenko according to the question / answer scheme. In accordance with the principle of dialogism on the basis of the research method, the traditional method of problem issues was used: «What steps did B. Grinchenko rise to success? What are the ways to bring education to the people? What skills do I need to have to become a publisher?»; innovative techniques «Steps to success» and «Pyramid of Achievements». Accordingly, models of schemes are represented in the form of steps and pyramids. The innovative type of work – the search task was implemented: «Complete the scheme with a word that summarizes Grinchenko's contribution as a teacher and publisher to the education of his native people». Answers of the first-year students were divers via personal imagination skills, which were stimulated by B. Grinchenko’s many-sided talent and confirmed the using of «Steps to success» technique. The article analyzes the results of the cultural competences formation for students of the University during the interactive excursion «Smart Museum of Borys Grinchenko», master-class and workshop were held. It is recommended for students undergoing pedagogical practice, to share knowledge about the pedagogical and educational heritage of Borys Grinchenko.